A Mapping Study of Intrusion Detection System - Wan Umar, Wan Ahmad Safwan; Salleh, Norsaremah (International Journal on Perceptive and Cognitive Computing, 2024)
The Network Security Monitoring System has been widely used to check many systems that supply services. A lot of monitoring tools have been developed to facilitate the monitoring of the network security. Since there are a lot of options to cater to our needs, this will cause a lot of time and resources to try each tool that is suitable with the system. In this research, we conducted a comparative analysis to analyse each tool presenting their advantages, disadvantages and the method used. The main objective of this research is to perform a systematic mapping study for the purpose to identify research topics related to network intrusion detection system, to assess the most frequently applied method of intrusion detection system, and to verify the types of cyber-attack that currently exist. Based on the 30 primary studies included in this mapping study, the findings indicated that the most intrusion detection system commonly used is the hybrid method and Data Injection has been the primary attack type in the existing system.